Characterizing human oxidative, anabolic and glycolytic metabolism in athletes with extreme physiologies - Schranner, D.; Wackerhage, H.; Weinisch, P.; Schlegel, J.; Bremer, S.; Scherr, J.; Römisch-Margl, W.; Riermeier, A.; Zelger, O.; Stöcker, F.; Artati, A.; Witting, M.; et al. (Sports Medicine - Open, 2026)
Background Regular physical activity is known to benefit health but the long-term effects of specific exercise training on human metabolism remain incompletely described. In this study, we comprehensively characterized the blood metabolomes of male athletes with distinct exercise-adapted metabolic profiles, comparing endurance athletes (n = 11), sprinters (n = 8), and natural body builders (n = 9) as models for highly oxidative, glycolytic, and anabolic metabolism, respectively.